Implementation of Free Expression Approach in Dance Learning for Developing Children’s Creativity: A Case Study at Kindergarten - Nuri Aprilia Handayani; Joko Pamungkas; Ika Budi Maryatun (Yayasan Keluarga Guru Mandiri, 2024)
In early childhood education, traditional dance instruction often relies heavily on imitation and structured routines, potentially limiting children's creative development. Recent research suggests that more open-ended, expressive approaches may better foster creativity and movement exploration in young learners. This case study investigates applying a free-expression approach in dance learning to develop children's creativity in kindergarten, which addresses the critical need to move away from imitative teaching methods. The research utilized a qualitative case study methodology. Data were collected through observations of eight teaching sessions recorded in field notes, interviews with teachers conducted in a semi-structured manner, the data recorded as interview notes, and document collection whose results were recorded as documentation notes. The data collection also involved student subjects of nine children aged five to six years for four weeks. The data were then analyzed using Milles and Huberman's flow, which consisted of data collection, reduction, presentation, and conclusion drawing. Data validity was guaranteed through observation, interviews, and triangulation of document studies. The results showed that the implementation process successfully passed through three phases (initial resistance, progressive integration, and emergent synthesis), indicating an effective teacher transition from demonstrator to facilitator. The pattern of children's creativity development varied based on their movement background. Analysis of creativity indicators showed measurable progress across all four dimensions (fluency, flexibility, originality, and elaboration), mainly when supported by appropriate environmental modifications. However, the systematic documentation of the implementation process provides a valuable framework that other institutions can adapt for their specific contexts while suggesting directions for future research in developing appropriate assessment tools for early childhood education.